2008
DOI: 10.1016/j.jvs.2008.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of combined common femoral endarterectomy and iliac stenting/stent grafting for occlusive disease

Abstract: Combined CFA endarterectomy with iliac intervention yield acceptable long-term results. The use of stent grafts compared with bare stents is associated with improved primary patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
113
2
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(123 citation statements)
references
References 26 publications
2
113
2
6
Order By: Relevance
“…Surgical procedures were as reported in the literature. 7,13,14,33 Most of the procedures (71%) occurred under local anesthesia, and the remaining under general anesthesia. Because of concern of perioperative bleeding complications caused by the use of anticoagulant drugs it is recommended that the use of epidural or spinal anesthesia be avoided.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical procedures were as reported in the literature. 7,13,14,33 Most of the procedures (71%) occurred under local anesthesia, and the remaining under general anesthesia. Because of concern of perioperative bleeding complications caused by the use of anticoagulant drugs it is recommended that the use of epidural or spinal anesthesia be avoided.…”
mentioning
confidence: 99%
“…Recently, several investigators have published results on several types of combined treatments for various patterns of iliac, femoral, and infrapopliteal diseases with promising outcomes. [7][8][9][10][11][12][13][14] Most reports discussed hybrid bypass surgery and endovascular surgery. [7][8][9][10][11]13 Although few reported femoral artery endarterectomy combined with iliac artery endovascular therapy, 12,14 which did not include the infrainguinal lesions.…”
mentioning
confidence: 99%
“…Сердечно-сосудистые заболевания / Cardiovascular medicine В настоящее время во всем мире для лечения ате-росклеротических поражений подвздошных арте-рий все шире применяются эндоваскулярные вме-шательства, включающие баллонную дилятацию и стентирование [1,2,3,4,5,6,7,8,9,10,11,12]. Однако наряду с ними существует другой малотравматич-ный способ лечения, приобретающий все большую популярность -эндартерэктомия при помощи раз-личных петель и колец (ПЭАЭ).…”
Section: том 4 №5 / 2017unclassified
“…ПЭАЭ возможно выполнять не только при ограниченных окклюзиях и стенозах артерий, но и при продленных. А так же данное вмешательство более радикально, чем эндо-васкулярные операции [1,6,9,10,12].…”
Section: том 4 №5 / 2017unclassified
“…It has been suggested that covered stents may be useful for lesions involving the distal aorta and for iliac arteries that are being treated with kissing stents [32,33]. The disadvantage of ePTFE covered stents is the difficult deliverability due to their stiffness, which often requires larger sheaths and may predispose patients to access site complications.…”
Section: Covered Stentsmentioning
confidence: 99%